An evaluation of the impact of the Social Mobility Foundation programmes on employment outcomes - Christine Farquharson; Ellen Greaves (Institute for Fiscal Studies (IFS), 2021)
While there is broad agreement in the UK on the importance of social mobility, current evidence suggests that social background is more strongly related to outcomes in the UK than in many other developed countries. Educational attainment, university choices, occupation and earnings are all influenced by socio-economic background. These effects show up at each stage of the lifecycle: graduateswho attended a state school areless likely than their privatelyeducated classmatesto enter a professional occupation, even when they earn the same grades on the same degree at the same university (Macmillan, Tyler and Vignoles, 2015). And within a profession, workers from disadvantaged backgrounds still earn less than their colleagues (Laurison and Friedman, 2016).In response to these challenges, the Social Mobility Foundation (SMF) was established to make a practical contribution to social mobility in the UK by encouraging access to high-status universities and professional occupations for high-attaining pupils from disadvantaged backgrounds. They offer programmes involving mentoring, internships, support with university applications, and access to skills development workshops.This report evaluates the impact that theSMF's programmes havehad on participants' employment outcomes, including their overall employment rate and the sector and skill level of their first job after university. We compare SMFparticipants witha matched control group of graduates who havesimilar observable characteristics, including performance at A-level and parental background.
Keywords: 330